Design and characterisation of bodipy sensitizers for dye-sensitized NiO solar cells. Issue 2 (10th December 2015) - Summers, Gareth H.; Lefebvre, Jean-François; Black, Fiona A.; Stephen Davies, E.; Gibson, Elizabeth A.; Pullerits, Tönu; Wood, Christopher J.; Zidek, Karel
Abstract : A series of photosensitizers for NiO-based dye-sensitized solar cells is presented. Abstract : A series of photosensitizers for NiO-based dye-sensitized solar cells is presented. Three model compounds containing a triphenylamine donor appended to a boron dipyrromethene (bodipy) chromophore have been successfully prepared and characterised using emission spectroscopy, electrochemistry and spectroelectrochemistry, to ultimately direct the design of dyes with more complex structures. Carboxylic acid anchoring groups and thiophene spacers were appended to the model compounds to provide five dyes which were adsorbed onto NiO and integrated into dye-sensitized solar cells. Solar cells incorporating the simpleBodipy-CO2 H dye were surprisingly promising relative to the more complex dye4 . Cell performances were improved with dyes which had increased electronic communication between the donor and acceptor, achieved by incorporating a less hindered bodipy moiety. Further increases in performances were obtained from dyes which contained a thiophene spacer. Thus, the best performance was obtained for7 which generated a very promising photocurrent density of 5.87 mA cm −2 and an IPCE of 53%. Spectroelectrochemistry combined with time-resolved transient absorption spectroscopy were used to determine the identity and lifetime of excited state species. Short-lived (ps) transients were recorded for4, 5 and7 which are consistent with previous studies. Despite a longer lived (25 ns) charge-separated state for6 /NiO, there was no increase in the photocurrent generated by the corresponding solar cell.